2013
DOI: 10.1093/infdis/jit018
|View full text |Cite
|
Sign up to set email alerts
|

Concordance and Transmission of Human Papillomavirus Within Heterosexual Couples Observed Over Short Intervals

Abstract: High rates of concordance shortly after intercourse suggest that some DNA detections in the genital area are contaminants from a partner and not established HPV infections. Female-to-male transmission appeared more common than male-to-female transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 26 publications
8
60
2
1
Order By: Relevance
“…All of those studies also reported higher specificities for the AHPV test, which is supported by our data showing a significantly (P Ͻ 0.001) increased specificity of 96.1% for the AHPV test, compared to 94.9% for the HC2 test (difference, 1.2% [95% CI, 0.87% to 1.48%]). This might be due to the fact that, by measuring mRNA levels, the AHPV assay detects actively infected cells, whereas DNA-based assays such as the HC2 assay do not distinguish between intracellular viral DNA and extracellular viral DNA, which may represent contamination (e.g., with virus particles), as shown previously in transmission studies in young couples (30).…”
Section: Discussionmentioning
confidence: 96%
“…All of those studies also reported higher specificities for the AHPV test, which is supported by our data showing a significantly (P Ͻ 0.001) increased specificity of 96.1% for the AHPV test, compared to 94.9% for the HC2 test (difference, 1.2% [95% CI, 0.87% to 1.48%]). This might be due to the fact that, by measuring mRNA levels, the AHPV assay detects actively infected cells, whereas DNA-based assays such as the HC2 assay do not distinguish between intracellular viral DNA and extracellular viral DNA, which may represent contamination (e.g., with virus particles), as shown previously in transmission studies in young couples (30).…”
Section: Discussionmentioning
confidence: 96%
“…Transmission from man to woman or woman to man has been evaluated in six of the recent studies shown in Table 1. Three of the studies have detected that transmission of α-HPV occurs more likely from man to woman [4, 19, 20] and two from woman to man [16, 17]. The only study detecting β- and γ-HPV infection within a 6-week follow-up, so far, has not found any difference in transmission between sexes [6].…”
Section: Hpv Transmission In Heterosexual Couplesmentioning
confidence: 99%
“…According to 13 case reports or case series and 9 larger population-based retrospective studies, a small trend of increased risk was found (1–3%). Higher concordance rates have also been related to short abstinence times before sampling [6, 16]. …”
Section: Risk Factors For Hpv Concordance In Heterosexual Couplesmentioning
confidence: 99%
“…HPV DNA has been detected from the hand and finger nails of sexually active individuals. 12,13 Since these studies are based on DNA detection and not confirmation of active infections, it is unknown whether these HPV DNA detections reflect live viral particles which can be transmitted. A recent study of 14-to 17-year-old girls reported that HPV DNA was detected in 10 of 22 girls from vaginal swabs prior to reporting vaginal intercourse.…”
Section: Discussionmentioning
confidence: 99%